8. DESIGN OF AN IOT-BASED REMOTE MONITORING SYSTEM FOR YOGYAKARTA AIRPORT LOCALIZER WITH AUTOMATIC CHANGEOVER AND REAL-TIME NOTIFICATION FEATURES - Muchammad Furqon; Oki Tri Rizki; Rakin Ghiyat; Kurniawan; Rayhan Kemal; Tia Tsania (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This research on remote monitoring design aims to determine the condition andcontrol the Localizer equipment in normal or alarm conditions. It can also assist in changingover during ground checks, accessible via smartphone using the Blynk app. This design usesan optocoupler sensor to detect the electrical current flowing through the LEDs on the LocalizerRemote Control Unit (RCU). This allows the indicator readings to be sent to the Internet ofThings (IoT) using a NodeMCU Wi-Fi module that communicates serially with an Arduino. TheIoT functions to display real-time conditions and control the Localizer equipment in normal oralarm conditions, accessible via smartphone using the Blynk app. The tool I will design is anInternet of Things-based remote monitoring localizer. It is hoped that this remote monitoringtool will facilitate technicians in determining the condition of the Localizer and assist in changingover during ground checks.